A Two‐Step Heat Treatment to Eliminate the Micro‐Segregation of Ti–45Al–8.5Nb–0.2W–0.2B–0.02Y Alloy1 . Issue 7 (31st March 2016) - Zhang, Yan; Kou, Hongchao; Yang, Guang; Tang, Bin; Xue, Xiangyi; Li, Jinshan
Abstract : Micro‐segregation in high Nb‐containing TiAl alloys usually causes the inhomogeneous of microstructure and the initiation of microcracks. In this paper, a novel two‐step heat treatment (HT) approach is proposed based on the phase transformation sequence to remove the micro‐segregation. In the first step, Ti–45Al–8.5Nb–0.2W–0.2B–0.02Y alloy is annealed in 1470 °C for 30 min to eliminate the solidification segregation and reduce the stability of β phase. The alloy is then cooled to 1340 °C, slightly above the α + β transus (Tα + β ) for about 60 min in order to remove the β‐segregation. Results show that the homogeneity of the lamellar colony is improved after the two‐step HT. Abstract : Two kinds of high Nb–TiAl alloy are subjected to a novel two‐step heat treatment approach. The upper images show the initial microstructure, which show serious β segregation and solidification. After heat treatment, both β and solidification segregation are eliminated (down‐left and down‐right, respectively).